Pemanfaatan Poster sebagai Media Pembelajaran Kreatif untuk Generasi Z - Raisa Adilla; Khairunnisa Khairunnisa; Mardiana Mardiana; Jasiah Jasiah (Lembaga Yasin AlSys, 2025)
Student learning interest, particularly among Generation Z, tends to be low due to teaching methods that are often unengaging and not fully aligned with the characteristics of a generation raised in a digital ecosystem. This generation demonstrates a strong preference for visual content, rapid access to digital information, and an independent, interactive learning style. This study aims to explore the use of posters as an innovative learning medium suited to the traits of Generation Z. A descriptive qualitative method was employed using a case study approach, based on a literature review from various relevant journals. The findings indicate that posters function not only as visual aids but also as creative media capable of linking students’ learning needs with instructional goals. When used effectively, posters foster active student engagement and enhance material comprehension through visualization. The study concludes that teachers need to improve their competencies in designing innovative visual media that are relevant to technological advancements. The implications of these findings highlight the importance of supporting teachers in developing adaptive, visual-based learning strategies to address the educational challenges of the digital era.